Thrombus Imaging Using 3D Printed Middle Cerebral Artery Model and Preclinical Imaging Techniques: Application to Thrombus Targeting and Thrombolytic Studies - Vítečková Wünschová, Andrea; Novobilský, Adam; Hložková, Jana; Scheer, Peter; Petroková, Hana; Jiřík, Radovan; Kulich, Pavel; Bartheldyová, Eliška; Hubatka, František; Jonas, Vladimír; Mikulík, Robert; Malý, Petr; et al. (Pharmaceutics, 2020)
Diseases with the highest burden for society such as stroke, myocardial infarction, pulmonary embolism, and others are due to blood clots. Preclinical and clinical techniques to study blood clots are important tools for translational research of new diagnostic and therapeutic modalities that target blood clots. In this study, we employed a three-dimensional (3D) printed middle cerebral artery model to image clots under flow conditions using preclinical imaging techniques including fluorescent whole-body imaging, magnetic resonance imaging (MRI), and computed X-ray microtomography (microCT). Both liposome-based, fibrin-targeted, and non-targeted contrast agents were proven to provide a sufficient signal for clot imaging within the model under flow conditions. The application of the model for clot targeting studies and thrombolytic studies using preclinical imaging techniques is shown here. For the first time, a novel method of thrombus labeling utilizing barium sulphate (Micropaque®) is presented here as an example of successfully employed contrast agents for in vitro experiments evaluating the time-course of thrombolysis and thus the efficacy of a thrombolytic drug, recombinant tissue plasminogen activator (rtPA). Finally, the proof-of-concept of in vivo clot imaging in a middle cerebral artery occlusion (MCAO) rat model using barium sulphate-labelled clots is presented, confirming the great potential of such an approach to make experiments comparable between in vitro and in vivo models, finally leading to a reduction in animals needed.
Keywords: thrombus imaging; MRI; microCT; MCAO; rtPA; thrombolysis; fibrin targeting; fluorescence imaging; 3D printing